Seismotectonic study of northern Iraq and surroundings from waveform inversion method - Ahmed, Omar Q. (Sulaimani Journal for Pure and Applied Sciences, 2013)
This paper is to estimate the seismic velocities beneath the northern Iraq seismographic (NISN) stations and the surrounding regions using the recorded data from these stations. One and two-dimensional crustal and upper mantle structures determined using the waveform inversion method through different paths within the region. This technique applied to regional waveforms traversing Turkish-Iranian Plateau and the northern Arabian platform. The final models resulted from the inverted parameters (layer thickness, shear wave velocity, and attenuation) have been analysed. The results show an average crustal thickness of 30 km with bulk shear velocity of 3.9 km/sec and the event paths encounter thick sediments of the foredeep. Phase match filtering used to isolate the fundamental mode from other signals. The results indicate that the depth of the Moho varies considerably beneath NISN. It is relatively shallow (35–45 km) to the northwest and deeper (50–60 km) under the south-eastern portion of the area. The shear wave velocity values are higher in the platform than in the plateau and generally variations in crustal thickness and velocity found between the northern Arabian platform and the Turkish plateau.
Keywords: inversion; layer thickness and shear wave velocity